PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KINERJA PERUSAHAAN: THE EFFECT OF COMMITTEE AUDIT CHARACTERISTICS ON FIRM PERFORMANCE - Chindy Pebrika Perangin-Angin; Mayla Khoiriyah; Raja Adri Satriawan; Ulfa Afifah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study empirically examines the impact of audit committee size variables, financial expertise and frequency of audit committee meetings and company performance. Population of this sudy was firms listed in Bursa Efek Indonesia (BEI) and The sample was company from Basic and Chemical Industry from 2014-2020 with 295 total observation. The company's performance uses TobinsQ measurements. Regression analysis using panel data and stata 17 application identified that the size of the audit committee and the financial expertise of the audit committee had a significant positive effect on the company's performance. On the other hand, the frequency of audit committee meetings that are routinely held every year was found to have a positive insignificant effect on the company's performance. This research contributes to the company's performance. First, it shows the extent of the performance of basic industrial and chemical companies listed on the Indonesia Stock Exchange. Second, the study adds to the existing literature on the impact of audit committee attributes on company performance by using a focus of one measurement of company performance and specifically audit committees that were previously not specific. Third, this study is expected to provide feedback to regulators of basic and chemical industry companies on the current regulations on the requirements of being an audit committee in basic and chemical industrial enterprises. Finally, this study raises some issues of interest to other researchers who are or will be conducting research in this field.